2007
DOI: 10.1186/1471-2164-8-241
|View full text |Cite
|
Sign up to set email alerts
|

A complete mitochondrial genome sequence of the wild two-humped camel (Camelus bactrianus ferus): an evolutionary history of camelidae

Abstract: Background: The family Camelidae that evolved in North America during the Eocene survived with two distinct tribes, Camelini and Lamini. To investigate the evolutionary relationship between them and to further understand the evolutionary history of this family, we determined the complete mitochondrial genome sequence of the wild two-humped camel (Camelus bactrianus ferus), the only wild survivor of the Old World camel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 23 publications
(21 reference statements)
2
52
0
Order By: Relevance
“…Unlike the other 21 tRNA genes, the tRNA Ser(GCU) gene cannot form a typical cloverleaf structure because it lacks the appropriate sequence to form the dihydrouridine arm and loop. This unusual secondary structure is also found in many mt genomes from other vertebrates, including bear, coyote, dogs, Eurasian otter, and wild camel (Peng et al, 2007;Hou et al, 2007;Cui et al, 2007;Hwang et al, 2008 Leu(UAG) ], which may be restored through RNA-editing mechanisms.…”
Section: Ribosomal and Transfer Rna Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the other 21 tRNA genes, the tRNA Ser(GCU) gene cannot form a typical cloverleaf structure because it lacks the appropriate sequence to form the dihydrouridine arm and loop. This unusual secondary structure is also found in many mt genomes from other vertebrates, including bear, coyote, dogs, Eurasian otter, and wild camel (Peng et al, 2007;Hou et al, 2007;Cui et al, 2007;Hwang et al, 2008 Leu(UAG) ], which may be restored through RNA-editing mechanisms.…”
Section: Ribosomal and Transfer Rna Genesmentioning
confidence: 99%
“…The largest (997 bp) non-coding region, CR, was identified between the tRNA Pro and tRNA Phe genes, with an A+T content of 62.2%. By comparing the complete CR region in M. himalayana with the corre-sponding CRs in other mammalians (Sbisa et al, 1997, Cui et al, 2007Hwang et al, 2008), we could compartmentalize the CR of M. himalayana into three domains: domain (D)-I, -II, and -III (Figure 3), corresponding to the termination-associated sequence domain (TAS), the central conserved domain (CD), and the conserved sequence block domain (CSB) (Sbisa E, 1997). We found a termination-associated sequence (TAS-A) and six conserved sequence blocks (CSB1 and B-F), which contain regulatory sequences controlling replication and transcription.…”
Section: Non-coding Regionsmentioning
confidence: 99%
“…Stem mismatches seem to be a common phenomenon for mitochondrial tRNA genes and are probably repaired via a post-transcriptional editing process (Lavrov et al, 2000). The tRNA Ser(AGY) found in the C. auratus mitogenome had no recognizable DHU stem, which is similar to almost all vertebrate mitogenomes (e.g., Cui et al, 2007;Zhou et al, 2009;Cheng et al, 2011). Although this tRNA Ser(AGY) has been described as a pseudo-gene to explain its unusual structure, Ohtsuki et al (2002) suggested that it could also perform its function by adjusting its structural conformation to fit the ribosome in a similar way to that of usual tRNAs in the ribosome.…”
Section: General Features Of the C Auratus Var Pingxiangnensis Mitomentioning
confidence: 88%
“…pingxiangnensis mitogenome (Table 2), which was typical of lengths found for other bony fishes (781-1200 bp). This AT-rich region usually evolves relatively fast as a result of few selective constraints and is identified as the source of size variation in the whole mitogenome, whereas its control elements that are related to regulatory functions are known to be highly conserved (Cui et al, 2007).…”
Section: Comparative Analysis Of Control Region Features In Cyprinidsmentioning
confidence: 99%
“…Abo-Elazm (2009) identified some camel breeds depending on biochemical genetic fingerprinting of each breed using protein polymorphism, as well as randomly amplified polymorphic DNA and simple sequence repeats. Cui et al (2007) studied a complete mitochondrial genome sequence of the wild two-humped camel. They found that the mitochondrial genome sequence was 16,680 bp for Camelus bactrianus Ferus containing 13 protein-coding, two rRNA, and 22 tRNA genes as well as a typical control region; this basic structure T is shared by all metazoan mitochondrial genomes.…”
Section: Genetic Engineering and Biotechnologymentioning
confidence: 99%